Immunomodulation of Host Chitinase 3-Like 1 During a Mammary Pathogenic Escherichia coli Infection - Breyne, Koen; Steenbrugge, Jonas; Demeyere, Kristel; Lee, Chun Geun; Elias, Jack A.; Petzl, Wolfram; Smith, David G. E.; Germon, Pierre; Meyer, Evelyne (Frontiers in Immunology, 2018)
Chitin is a N-acetyl-D-glucosamine biopolymer that can be recognized by chitin binding proteins. Although mammals lack chitin synthase, they induce proteins responsible for detecting chitin in response to bacterial infections. Our aim was to investigate whether chitinase 3-like 1 (CHI3L1) has a potential role in the innate immunity of the Escherichia coli (E. coli) infected mammary gland. CHI3L1 protein was found to be secreted in whey of naturally coliform affected quarters compared to whey samples isolated from healthy udders. In addition, gene expression of CHI3L1 was confirmed in udder tissue of cows experimentally infected with a mammary pathogenic E. coli (MPEC) strain. Despite the known anatomical differences, the bovine udders’ innate immune response was mimicked by applying an experimental mouse model using MPEC or non-MPEC isolates. The effect of CHI3L1 expression in the murine mammary gland in response to coliform bacteria was investigated through the use of CHI3L1-/- mice as well as through treatment with either a pan-caspase inhibitor or chitin particles in wild type mice. The local induction of CHI3L1 post-infection with different E. coli strains was demonstrated to be independent of both, bacterial growth and mammary interleukin (IL)-8 levels. Indeed, CHI3L1 emerged as a regulator impacting on the transcytosis of Ly6G-positive cells from the interstitial space into the alveolar lumen of the mammary tissue. Furthermore, CHI3L1 was found to be upstream regulated by caspase activity and had a major downstream effect on the local pro-inflammatory cytokine profile including IL-1beta, IL-6 and RANTES/CCL5. In conclusion, CHI3L1 was demonstrated to play a key role in the cytokine and caspase signaling during E. coli triggered inflammation of the mammary gland.